The Dynamics of Foreign Direct Investment in Romania After EU Accession - Nicoleta Rusu (CES Working Papers, 2010)
Identification of potential investment of the countries in the current context is one of the main important problem of the world economy because the investments, particularly foreign ones, is considered the key factor for economic growth and development. Foreign direct investments are an alternative source for financing the national economy, with a tendency in recent years of a positive effect on the Romanian economy. This paperwork highlights the role of foreign direct investment in Romania's economical growth potential, with major impact on employment, on the economic modernization, technology transfer and on the living standards. At the same time the article analyzed and highlights the contains of the current trend of foreign direct investments, structure and dynamics after Romania joined the European Union and their geographical distribution on the main development regions.
Keywords: 330; foreign direct investments; role of foreign direct investments; development regions; economic growth